The Relationship Between Self-Efficacy and Motivation for Achievement in Memorizing The Quran in Students at Wonosalam Jombang Boarding School - Nabila, Nuhan; Affandi, Ghozali Rusyid (Syntax Literate, 2024)
This study aims to explore the relationship between self-efficacy and achievement motivation in memorizing the Quran among students (santri) at Wonosalam Islamic Boarding School in Jombang. A quantitative method was employed with a sample size of 80 students. Reliability tests conducted through Cronbach's alpha yielded values of 0.842 for self-efficacy and 0.797 for achievement motivation. Descriptive analysis results indicated that the majority of students had moderate levels of self-efficacy and achievement motivation. Pearson correlation test revealed a significant positive relationship between self- efficacy and achievement motivation (r = 0.309, p < 0.05), suggesting that higher self- efficacy corresponds to higher achievement motivation, and vice versa. These findings support the theory that self-efficacy influences achievement motivation. The implication is that enhancing the self-efficacy of students can be a strategy to boost their achievement motivation in memorizing the Quran at the Islamic Boarding School.